PHEOCHROMOCYTOMA: AN OVERLOOKED CONDITION IN HYPERTENSIVE DISORDER IN PREGNANCY - TK, Wong; M, Saieehwaran; R, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Pheochromocytoma is a rare tumour derived from chromaffin cells of the adrenal medulla or extra-adrenal paraganglia. It is a rare cause of secondary hypertension and is commonly overlooked in pregnancy due to limitations in investigation during pregnancy. It occurs in 0.1-1% of the hypertensive population and is even more rare in pregnancy. CASE A 33-year-old pregnant female with a parity of 8, diagnosed with chronic hypertension and with a history of severe preeclampsia in her previous pregnancy, presented again at 34 weeks of gestation with severe preeclampsia. Blood pressure was 179/124, and heart rate ranged from 100 to 120 bpm. Urinary examination revealed proteinuria. Despite treatment with conventional antihypertensives, her blood pressure remained uncontrolled. Thus, she was planning for emergency C-section. Intubation was done due to cardiorespiratory compromise, which was complicated by cardiac arrest. She was successfully resuscitated. Computed tomography (CT) of the adrenal glands showed a large, heterogeneously enhancing right adrenal lesion measuring 7.4 x 7 x 8 cm. Twenty-four-hour urinary catecholamine levels were elevated, with normetanephrine at 67.80 umol/ day (0-2.13), metanephrine at 97.30 umol/day (0-1.62), and 3-methoxytyramine at 7.60 umol/day (0.1-1.79). The classical presentation of pheochromocytoma with paroxysmal hypertension, headaches, sweating, and palpitations may not be simultaneously present, especially during pregnancy. Labile BP and difficult to control hypertension should raise suspicion for pheochromocytoma, to prompt appropriate investigations that will facilitate an early diagnosis. Measurements of urinary or plasma catecholamines have reasonable sensitivity for detecting most pheochromocytomas, particularly in patients with sustained hypertension. Radioisotope scans, including iodine 131-labeled metaiodobenzylguanidine scanning, should be avoided during pregnancy due to foetal concerns and, if required, should be postponed until the postpartum period. CONCLUSION Pheochromocytoma in pregnancy is a life-threatening condition. Early suspicion and recognition are essential to prevent fetomaternal morbidity and mortality.